2007
DOI: 10.1007/s10681-007-9382-x
|View full text |Cite
|
Sign up to set email alerts
|

Amplified fragment length polymorphism as a tool for molecular characterization of almond germplasm: genetic diversity among cultivated genotypes and related wild species of almond, and its relationships with agronomic traits

Abstract: Amplified fragment length polymorphism (AFLP) analysis is a rapid and efficient method for producing DNA fingerprints and molecular characterization. Our objectives were to: estimate genetic similarities (GS), marker indices, and polymorphic information contents (PICs) for AFLP markers in almond cultivars; assess the genetic diversity of almond cultivars and wild species, using GS estimated from AFLP fingerprints and molecular characterization; and facilitate the use of markers in inter-specific introgression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 41 publications
8
65
0
Order By: Relevance
“…Our results showed that the PCoA data approximately corresponded to those obtained through cluster analysis. This is in agreement with other findings (DARVISHZADEH et al, 2010;KUMAR et al, 2009;SORKHE et al, 2007). Table 1 Conclusions 1.…”
Section: Resultssupporting
confidence: 93%
“…Our results showed that the PCoA data approximately corresponded to those obtained through cluster analysis. This is in agreement with other findings (DARVISHZADEH et al, 2010;KUMAR et al, 2009;SORKHE et al, 2007). Table 1 Conclusions 1.…”
Section: Resultssupporting
confidence: 93%
“…The PIC parameter is used in genetics as a measure of polymorphism for a marker locus (Roldán-Luiz et al 2000), the MI parameter is used to estimate the overall utility of each marker system (Sorkheh et al 2007) and EMR is used to evaluate whether a primer is effective (Powell et al 1996). The most appropriate primers to differentiate species/cultivars were the OPE01 in RAPDs and UBC844 in ISSRs since both presented the highest value of PIC, MI and EMR in both tissues (fruits and leaves).…”
Section: Resultsmentioning
confidence: 99%
“…and Ib is band informativeness and p i is the proportion of the accessions containing band; the polymorphism information content (PIC) according to Roldán-Ruiz et al (2000) where PIC i = 2f i (1 -f i ) (f i is the frequency of amplified allele and 1 -f i is the frequency of null allele of marker i); the effective multiplex ratio (EMR) following Powell et al (1996) where EMR is number of polymorphic products from a single amplification reaction; and the marker index (MI) following Sorkheh et al (2007) defined as the product of polymorphism percentage and PIC. Cluster analysis was done, applying an unweighted pairgroup method with arithmetic averages (UPGMA) based on a simple matching similarity matrix and SAHN subroutine to compute a principal coordinate (PCO) analysis through the NTSYS-pc Ver.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, various molecular markers such as sequence related amplified polymorphism (SRAP), amplified fragment length polymorphism (AFLP) and single nucleotide polymorphisms (SNP) have been used for almond genetic diversity assessment (Jing et al, 2013;Sorkheh et al, 2007;Wu et al, 2008). Microsatellites or simple sequence repeat markers (SSRs) are the preferred marker for a wide range of applications in genetics and plant breeding.…”
Section: Introductionmentioning
confidence: 99%